KERAGAAN GENOTIPE JAGUNG F14 DI LAHAN GAMBUT - Ragiman, Ragiman; Hidayat, Hidayat; zulfita, Dwi (Jurnal Sains Mahasiswa Pertanian, 2019)
This study aims to determine the performance of F14 corn genotype on peat soil. This research was carried out in Rasau Jaya II Village with C overflow. This research was conducted from 24 January 2018 to 02 June 2018. The experimental was designed in pattern to be used was a Randomized Block Design (RBD), consisting of 5 F14 genotypes and 1 Arjuna variety as a comparison. The number of groups is 5, so there are 30 plots of treatment. Treatments were en codel as follows: A = Arjuna Varietie (Controls) and F14 genotypes (B, C, D, E, F). The observational variables in this study include: Plant height (cm), male flowering age, female flowering age, harvest age, ear diameter (cm), number of rows per ear, weight of seedlings 14% (g), weight of seedlings (g) , The weight of 1,000 dry seeds (g), the weight of the dry seed strip (g). The maize genotype is good at Rasau Jaya II A, C, F, genotype B, D, E with poor performance. The result of this resenel are genotypes A, C, and F as good performance and genotypes B, D, and E are bad Performance at Rasau Jaya II.